Faktor-Faktor Yang Berhubungan Dengan Partisipasi Ibu Dalam Penimbangan Balita Di Wilayah Kerja Posyandu Kasih Ibu Lebak Bulus - Sabilly , Farhan; Khasanah, Tri Ardianti (Jurnal Gizi dan Kuliner, 2023)
Monitoring the growth of toddlers at the posyandu can be seen based on the coverage of the participation of mothers under five. Several factors can reduce interest in posyandu activities and low participation of mothers under five. The purpose of the study was to analyze the factors of participation of mothers in weighing toddlers in the working area of Posyandu Kasih Ibu Lebak Bulus using a quantitative research method with a cross-sectional design. A total of 50 mothers of children under five became the subject of research and data collection by filling out questionnaires. The results showed that only the mother’s work factor had a significant relationship with the mother’s participation in weighing toddlers at the Kasih Ibu Lebak Bulus Posyandu (p=0.023). It concluded that the involvement of parents in taking time from busy work to participate in weighing toddlers is very much needed so that the process of monitoring toddler growth can be carried out to prevent nutritional problems in children. Keywords: mother’s occupation; mother’s education, mother’s knowledge, mother’s age